2021
DOI: 10.1088/1361-6528/ac0190
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of graphene-based aerogel in the field of supercapacitor

Abstract: Graphene and graphene-based hybrid materials have emerged as an outstanding supercapacitor electrode material primarily because of their excellent surface area, high electrical conductivity, and improved thermal, mechanical, electrochemical cycling stabilities. Graphene alone exhibits electric double layer capacitance (EDLC) with low energy density and high power density. The use of aerogels in a supercapacitor is a pragmatic approach due to its extraordinary properties like ultra-lightweight, high porosity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 188 publications
0
26
0
Order By: Relevance
“…The 2D carbon has good physiochemical stability due to the high interconnected area formed by randomly overlapped 2D building blocks. 122 However, 2D layered carbons usually result in ineffective charge storage due to the restacking and agglomeration of nanosheets. One efficient way to resolve this problem is to insert foreign atoms into the carbon structure.…”
Section: Zinc-ion-based Hybrid Supercapacitormentioning
confidence: 99%
See 2 more Smart Citations
“…The 2D carbon has good physiochemical stability due to the high interconnected area formed by randomly overlapped 2D building blocks. 122 However, 2D layered carbons usually result in ineffective charge storage due to the restacking and agglomeration of nanosheets. One efficient way to resolve this problem is to insert foreign atoms into the carbon structure.…”
Section: Zinc-ion-based Hybrid Supercapacitormentioning
confidence: 99%
“…The added heteroatoms provide more active sites which enhance the charge storage capability. 122 Lu et al reported a new type of carbon material: 2D layered B/N codoped porous carbon (LDC). The LDC was synthesized by a facile intercalator (H 3 BO 3 )-guided pyrolysis technique by using acrylonitrile copolymer as the carbon source.…”
Section: Zinc-ion-based Hybrid Supercapacitormentioning
confidence: 99%
See 1 more Smart Citation
“…However, graphene has some limitations in its applications. Graphene has a large specific surface area of up to 2630 cm 2 /g 8 , which makes graphene easily agglomerate. If graphene is not uniformly distributed in the matrix, it will have an adverse impact on the properties of the material.…”
Section: Introductionmentioning
confidence: 99%
“…GO has abundant oxygen-containing functional groups [15,16], which allows it to be active in many reactions. The material synthesized as a raw material has high porosity [17,18], low density [19,20], and low thermal conductivity [21,22], which has attracted widespread attention.…”
Section: Introductionmentioning
confidence: 99%